Fractional Order Set-point Weighted PID Controller for pH Neutralization Process Using Accelerated PSO Algorithm - Bingi, K. (Springer Verlag, 2018)
Control of pH processes is highly challenging due to high nonlinearity and sensitivity around the equilibrium point. PID controllers being simple and the most widely used perform poorly with changing set-point and are limited to certain operating regions. Thus, they are inadequate for such applications without upgrading. In this paper, a fractional order set-point weighted PID (SWPI Î»D Î¼) controller is designed for pH neutralization process. The objective is to achieve adequate set-point tracking and effective load regulation through smooth control action. The controller parameters are tuned using accelerated particle swarm optimization which uses only global best position to achieve faster convergence. Simulation results show that for both standard and industrial configurations of the proposed approach, better performance in terms of set-point tracking, disturbance rejection and sensitivity to model parameter variation is achieved compared to PID, fractional order PID (PI Î»D Î¼) and SWPI-D. Â© 2017, King Fahd University of Petroleum & Minerals.